VIVALDI-CT shaping care home COVID-19 testing policy: A pragmatic cluster randomised controlled trial of asymptomatic testing compared to standard care in care home staff. - Oliver Stirrup; James Blackstone; Iona Cullen-Stephenson; Robert Fenner; Natalie Adams; Ruth Leiser; Maria Krutikov; Borscha Azmi; Nick Freemantle; Adam Gordon; Martyn Regan; Martin Knapp; et al. (PLoS ONE)
Background Non-pharmaceutical interventions were used widely in care homes for older people during the COVID-19 pandemic, but there have been few randomised trials to support policy decisions. We aimed to evaluate the effect of biweekly asymptomatic staff testing with support funding for sick pay and agency staffing on the clinical outcomes of residents. Methods We conducted a cluster randomised unblinded superiority trial, aiming to recruit up to 280 residential and/or nursing homes in England providing care to adults aged >65 years. Homes were randomised 1:1 to the control arm, which followed national testing policy (comprising symptomatic plus outbreak testing at trial initiation) or intervention (additional twice weekly asymptomatic staff testing for SARS-CoV-2, staff sick pay and agency backfill). Outcomes were evaluated using health data from routine national datasets in combination with aggregate data from participating homes. The primary outcome was the incidence of COVID-19-related hospital admissions in residents. Results The trial was conducted from January to August 2023, with 41 care homes randomised to intervention and 40 randomised to control included in the analysis. The trial was stopped early as it was not adequately powered for the primary outcome due to site recruitment and primary outcome events being substantially lower than expected. There was no significant difference in the primary outcome of resident COVID-linked hospital admission incidence between intervention and control arms (22.7/1000 person-years vs 15.0/1000 person-years, incidence rate ratio 1.19, 95%CI 0.55-2.58, P = 0.66; incidence rate difference 4.0, 95%CI -14.3 to 22.2). Trial set up took less than three months. Most trial outcomes were derived from routinely collected data. Recorded uptake of staff testing in the intervention arm was low (mean per home each week 14.4%). Conclusion This trial was not well-powered to evaluate the impact of the intervention on the primary outcome, and recorded uptake of staff testing was low. However, our pre-existing care home network underpinned by linked routinely collected data provides a model for more agile interventional studies in the care home setting. Clinicaltrials.gov registration NCT05639205.